AKTIVITAS FISIK DAN PERUBAHAN SIKLUS MENSTRUASI - Eduarna, Mutiara Suryani; Pramana, Yoga; Rahmawati, Nadia; Neri, Ervina Lili; Putri, Triyana Harlia (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
The menstrual cycle is one aspect of assessing female reproductive function, changes in the menstrual cycle can occur in women in their 20s due to irregular ovulation phases, changes in the menstrual cycle are influenced by several factors, one of which is physical activity. Physical activity of Nursing Study Program students at Tanjungpura University Pontianak varies from studying in class, laboratory, clinical practice in hospitals, other activities such as exercising. The purpose of this study was to determine the correlation between physical activity and changes in the menstrual cycle. This study is a quantitative study with a cross sectional approach on 100 respondents with total sampling technique, and data collection using IPAQ questionnaire and menstrual cycle questionnaire. Data analysis used frequency distribution and chi-square test. Physical activity of female students was mostly in the high category as many as 76 respondents (76.0%) of 100 respondents, the menstrual cycle of female students was mostly irregular as many as 80 respondents (80.0%) of 100 respondents. The results of the chi-square test showed that there was no correlation between physical activity and changes in the menstrual cycle in nursing students of Tanjungpura University Pontianak, with a p-value of 0.292 (p-value> 0.05), the correlation coefficient was positive with a value of 0.105. There is no correlation between physical activity and changes in the menstrual cycle of nursing students of Tanjungpura University Pontianak.